IMPLEMENTATION OF CHORALES BASED ON THE COLLECTION OF LEIPZIG CHORALES BWV 651-668 BY J. S. BACH (Heritage, 2025)
Bach’s chorale preludes from the collection Leipzig Chorales BWV 651-668 offer a wide spectrum of musical approaches, but they all retain the basic structure and theological basis – processing of Protestant chorale (hymns). The similarities between the preludes rest on their fidelity to the original chorale melody which is present in the soprano or pedal, or developed in other voices varying the theme in different ways (ornamentation, harmonization, fugal approach).Chorales are implemented in preludes solely by means of the polyphonic technique, starting with the developed counterpoint lines to theme imitation and fugued melody treatment, where the chorale melody is elaborated in various voices through counterpoint phrases. The individual differences are reflected in the rhythmic treatment, complex harmonic arrangements, fuguing techniques and variations, as well as in the dynamics. Bach „plays“ with various musical approaches in each prelude, adjusting chorale to the specific emotional and liturgic context. Each prelude in this cycle shows Bach’s skill of polyphonic processing of chorale, with various approaches that enable deep emotional and technical depth of music.
Keywords: chorale, prelude, Leipzig Chorales, ornamented chorale, cantus firmus technique, imitation, fugal approach.